Rapid emergence of highly variable and transferable oxazolidinone and phenicol resistance gene optrA in German Enterococcus spp. clinical isolates - Bender, Jennifer K.; Fleige, Carola; Lange, Dominik; Klare, Ingo; Werner, Guido (International journal of antimicrobial agents, 2018)
•optrA-positive and linezolid-resistant Enterococcus spp. are on the rise.•Multiple variants of the optrA gene exist.•optrA was detected in various plasmid backgrounds and the bacterial chromosome.•optrA is easily transferred to other pathogenic bacteria. The number of linezolid-resistant Enterococcus spp. isolates received by the National Reference Centre for Staphylococci and Enterococci in Germany has been increasing since 2011. Although the majority are E. faecium, clinical linezolid-resistant E. faecalis have also been isolated. With respect to the newly discovered linezolid resistance protein OptrA, the authors conducted a retrospective polymerase chain reaction screening of 698 linezolid-resistant enterococcus clinical isolates. That yielded 43 optrA-positive strains, of which a subset was analysed by whole-genome sequencing in order to infer linezolid resistance-associated mechanisms and phylogenetic relatedness, and to disclose optrA genetic environments. Multiple optrA variants were detected. The originally described variant from China (optrAWT) was the only variant shared between the two Enterococcus spp.; however, distinct optrAWT loci were detected for E. faecium and E. faecalis. Generally, optrA localized to a plethora of genetic backgrounds that differed even for identical optrA variants. This suggests transmission of a mobile genetic element harbouring the resistance locus. Additionally, identical optrA variants detected on presumably identical plasmids, that were present in unrelated strains, indicates dissemination of the entire optrA-containing plasmid. In accordance, in vitro conjugation experiments verified transfer of optrA plasmids between enterococci of the same and of different species. In conclusion, multiple optrA variants located on distinct plasmids and mobile genetic elements with the potential for conjugative transfer are supposedly causative for the emergence of optrA-positive enterococci. Hence, rapid dissemination of the resistance determinant under selective pressure imposed by extensive use of last-resort antibiotics in clinical settings could be expected.